Performance Analysis of 2D and 3D Fluid Flow Modelling Using Lattice Boltzmann Method - Fourier Dzar Eljabbar Latief; Umar Fauzi (Indonesian Journal of Physics, 2007)
Several studies have been conducted to observe properties of fluid flow in materials using the Lattice Boltzman Method (LBM). There are two widely used lattice model, the D2Q9 for the 2D simulation, and the D3Q19 for the 3D simulation. Our particular interest is to study the velocity map both using the 2D and the 3D simulation, using the same object. The aim of this study is to evaluate effectiveness and efficiency of both methods. In our simulation, the velocity profile between the 2D and 3D models differs greatly (mean error 30.4%) if the object has complex lateral structure (the shape along the z-axes differs greatly), while for the less complex object, the profile has only 1.4% of mean error. The computing time for the 3D model took 13 times longer than the simulation of the 2D model. The result from the comparison of both methods concludes that the simplification of fluid flow simulation of 3D objects into 2D objects should be taken carefully, for in some cases, the simplification is not quite appropriate.